The Credit Channel of Capital Tax Policy - Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
A neoclassical growth model is augmented by a corporate sector, financial intermediation, and a set of tax rates. In this setting, capital structure is determined by the interplay between an advantage of debt finance resulting from the tax system and a disadvantage resulting from asymmetric information and the entailed agency costs. Effects of capital tax reforms are investigated with a special focus on the credit channel that operates through the finance decision of firms. The theoretical part of the article derives which financial and real effects of private and corporate income tax policies can be expected. Using a calibration with U.S. data, the applied part demonstrates that tax cuts cause significant adjustments of capital structure. Nevertheless, the credit channel creates relatively small effects of tax reforms on consumption, investment, and growth.
Keywords: H30; O16; E62; E44; 330; Tax Reform; Corporate Finance; Agency Costs; Economic Growth